Delayed intracranial hemorrhage after trauma. (21st March 2021) - Mitra, Biswadev; Ruggles, Tomi; Seah, Jarrel; Miller, Charne; Fitzgerald, Mark C.
ABSTRACT: Introduction : Delayed Intracranial Hemorrhage (D-ICH), defined as finding of ICH on subsequent imaging after a normal computed tomography of the brain (CTB), is a feared complication after head trauma. The aim of this study was to determine the incidence and severity of D-ICH. Methods : This retrospective cohort study included patients that presented directly from the scene of injury to an adult major trauma center from Jan 2013 to Dec 2018. Results : There were 6536 patients who had an initial normal CTB and 23 (0.3%; 95%CI: 0.20–0.47) had D-ICH. There were 653 patients who had a repeat CTB (incidence of D-ICH 3.5%; 95%CI: 2.2–5.2). There was no significant association of D-ICH with age>65 years (OR 1.33; 95%CI: 0.54–3.29), presenting GCS <15 (OR 1.21; 95% CI: 0.52–2.80) and anti-platelet medications (OR 0.68; 95%CI: 0.26–1.74). Exposure to anti-coagulant medications was associated with lower odds of D-ICH (OR 0.23; 95%CI: 0.05–0.99). All cases of D-ICH were diffuse injury type II lesions on the Marshall classification. There were no cases that underwent neurosurgical intervention and no deaths were attributed to D-ICH. Conclusions : These results question observation of patients with head injury in hospital after a normal CTB for the sole purpose of excluding D-ICH.